Pearl - Malerman, Josh (Del Rey, 2021)
"From the New York Times bestselling author of Bird Box and Malorie Josh Malerman comes the legend of a strange new monster unlike any other in horror. There's something strange about Walter Kopple's farm. At first it seems to be his grandson, who cruelly murders one of Walter's pigs in an act of seemingly senseless violence. But then the rumors begin--people in town whisper that Walter's grandson heard a voice that commanded him to kill. And that the voice belongs to a most peculiar creature: Walter's pig, Pearl. Walter is not sure what to believe. He knows that he's always been afraid of the strangely malevolent Pearl. But as madness and paranoia grip the town and the townspeople descend on Walter's farm with violent wrath, Walter begins to wonder if true evil wears a human face"--